2016
DOI: 10.1016/j.baae.2016.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Environmental filtering, not local adaptation of established plants, determines the occurrence of seed- and bulbil-producing Poa alpina in a local flora

Abstract: Genetic variability among subspecies, ecotypes and populations is an important component of biodiversity, particularly when habitats are characterized by steep environmental gradients across short distances as in the landscape of the European Alps. In Poa alpina population differentiation is high due to polyploidy, facultative apomixis and the occurrence of seed-and bulbil-producing plants. We analysed microsatellite diversity of seed-and bulbil-producing populations from two nearby alpine grassland sites in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 59 publications
1
2
0
Order By: Relevance
“…This means that the gap between growth on NH 4 + and NO 3 depends on the cotyledons. The present results are consistent with those of Stöcklin and Armbruster (2016) which show that seed-producing individuals strongly differ molecularly from each other despite their proximity. Overall, it can be suggested that the preference of the nitrogen form by seedlings depends on the cotyledons which themselves depend on the availability and form of nitrogen in the rhizosphere of the mother plant during seed formation.…”
Section: Discussionsupporting
confidence: 92%
“…This means that the gap between growth on NH 4 + and NO 3 depends on the cotyledons. The present results are consistent with those of Stöcklin and Armbruster (2016) which show that seed-producing individuals strongly differ molecularly from each other despite their proximity. Overall, it can be suggested that the preference of the nitrogen form by seedlings depends on the cotyledons which themselves depend on the availability and form of nitrogen in the rhizosphere of the mother plant during seed formation.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, the elevational gradient has been considered as the most important factor in studies on phenotypic variation of plant species in mountains (e.g. Stöcklin et al 2009;Št'astná et al 2012;Kim and Donohue 2013;Scheepens and Stöcklin 2013;Gugger et al 2015;Hamann et al 2016;Stöcklin and Armbruster 2016;Sakurai and Takahashi 2016;Takahashi and Matsuki 2016). Plants can respond to elevational changes based on their morphological and physiological plasticity and through local adaptations (Hirano et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Substrate fertility may affect all climate response traits. For genotype tests, a most robust approach might be to sample replicated clonal fragments of different genets of the same species and replant them across the species’ home range [ 113 , 114 , 115 ]. Reciprocal transplantations of entire sods or monoliths can overcome the soil bias, but target species remain tied to the given neighborhood in the plant community.…”
Section: Concluding Commentsmentioning
confidence: 99%